PERAN SEO DALAM MENINGKATKAN RELIABILITAS PEMASARAN PRODUK VIA MEDIA ONLINE PADA FORUM MUSLIMAH DEPOK - Ahmad Maulana Irfanudin; Didi Sunardi; Ratna Sari; Imbron Imbron; Nariah Nariah (DEDIKASI PKM, 2020)
The purpose of Community Service Activities (PKM) is to carry out one of the three obligations of the Tri Dharma Perguruan Tinggi. In addition, it is expected that by serving the community, the existence of higher education institutions can contribute to the development and application of knowledge to the community. The method of activity used is to visit the Forum Muslimah Depok, Al-Awwal Mosque, addressed on Jalan Mawar Raya, Depok Jaya and look for problems that are in place so as to provide the right solution in motivating members who has business or UMKM in Depok, West Java, especially for Jama’ah Masjid Al Awwal Masjid Depok Jaya and gave training there on 01-03 October 2019. This training aims to develop the ability to increase marketing through online media with SEO methods and techniques (Search Engine Optimization) for Muslimah Forum members, Al-Awwal Mosque, Depok Jaya. The results of community service activities (PKM) obtained indicate that prior to the implementation of PKM, Depok Muslimah Forum members did not yet know the terms related to product marketing via online media, but after the implementation of activities known members of the Depok Muslimah Forum could understand the basics of content creation with simple SEO rules. PKM activities play a positive role in increasing the knowledge and skills of participants in creating SEO-based content The knowledge gained in Community Service this time is expected to be able to provide enthusiasm especially for the lecturers and other academicians of the University of Pamulang in providing material counseling, motivation and contributing to the public in and outside the campus environment of the University of PamulangKeywords: Content, Search Engine Optimization, Online